INTRACRANIAL TUBERCULOMAS AND CARIES SPINE:AN EXPERIENCE FROM CHILDREN’S HOSPITAL ISLAMABAD - Azam, Matloob; Bhatti, Nasera (Journal of Ayub Medical College Abbottabad, 2004)
Background: Pulmonary tuberculosis in infants and children in Pakistan is quite common. However, there is limited data about uncommon forms of tuberculous infection of central nervous system. Tuberculosis of nervous system is a serious disease and if not treated adequately, carries high morbidity and mortality. This study was undertaken to highlight the occurrence of relatively uncommon forms of tuberculosis in children. Methods: This was a retrospective review of the case records of the patients who were admitted in Children’s Hospital, Islamabad with the diagnosis of cerebral tubercloma or tuberculosis of spine between January, 1994 and August, 2002. Diagnosis was based on clinical features, history of contact with tuberculous patient, abnormalities on chest X-rays and neuroimaging studies of brain and spine. Results: Nine children had cerebral tuberculomas, six more than one and in five were bilateral. Eight had caries spine, 2 cervical, 4 thoracic and 2 lumbar regions. Three had been vaccinated with Bacillus-Calemette-Guerin and family history of tuberculosis was positive in 7 (41%) children. Nine (53 %) patients had evidence of pulmonary tuberculosis on chest x-ray. Ten computed scan brain, four magnetic resonance imaging, two spinal scan and two myelographic studies were performed. Three patients with tuberculomas and five with caries recovered and 8 were left with neurological deficit. One child with cerebral tuberculomas died. Conclusion: Intracranial tuberculomas and spinal tuberculosis are not rare problems in children. Early diagnosis and prompt antituberculous therapy are the most important factors for the favourable outcome. Key words: Tuberculosis, Tuberculoma, tuberculous spondylitis, Caries spine